Pattern extraction from northern Thai fabrics using flexibly matching segments: Sarong Teenjok and Lanna textiles - Vasantapan N. (2017)
© 2017 IEEE. This paper proposes a method with flexibility in detecting and recognizing northern Thai fabrics which usually include various delicate patterns or traceries. Due to delicacies in unique patterns of northern Thai fabrics, especially ones called Sarong Teenjok or even other Lanna textiles, flexibility in searching and detecting such patterns is required. Authors thus propose a method using some parameters allowed to be adjusted in order to add flexibility in pattern recognition. Thus, some small deviation, orientation, or different shadows and shades of the appeared traceries does not cause much problem. From experimental results, the proposed method still works very well in various challenging situations as mentioned, for example, in cases of having shadows in the input image, natural skewness or unnatural orientation of the fabrics, or some small deviation in pattern's colors of the traceries.